Model Pembelajaran Think Pair Share Untuk Meningkatkan Motivasi Belaajar IPAS Siswa Sekolah Dasar - Sari, Yofita; Hadi, Waluyo; Safitri, Nurrohmah (Jurnal keilmuan dan Kependidikan dasar, 2024)
Learning and teaching are closely interconnected, requiring a structured learning model. Think Pair Share (TPS), one of several learning models with the power to encourage students to think independently, collaborate, as well as share ideas. In the IPAS field of study in primary schools, increasing students' motivation is key as it can affect their learning outcomes. This study aims to examine the TPS model as an effort to improve elementary school students' learning in the IPAS subject area. This research is a qualitative study with literature sourced from Google Scholar, Semantic Scholar, and Mendeley databases. Data were collected through analysis involving several stages, such as summarizing data, identifying patterns, visualizing and developing data, and drawing conclusions related to research relevant to the topic. The research findings confirmed that the application of the model consistently increased students' learning motivation in learning IPAS. Thus, a learning model is needed to encourage students' learning motivation in the classroom by utilizing the TPS learning model